A SYSTEMATIC REVIEW OF THE EFFECT OF PSYCHOSOCIAL INTERVENTIONS ON POST-TRAUMATIC STRESS DISORDER EXPERIENCED BY RAPE SURVIVORS - Ibrahim, Lydia; Azaka, Lilian; Balogun, Shyngle (African Journal of Social and Behavioural Sciences, 2023)
Globally, 30% of women report having been the victim of sexual harassment, assault, or rape at some point in their lives, and 50% of rape victims report experiencing PTSD in addition to other physical and social consequences. There is a need to conduct an in-depth examination of these devastating multidimensional impacts due to their prevalence and the lack of organized data on the effectiveness of existing therapies, particularly those from Africa in order to bring attention to this threat. This study therefore attempts to compile data on the psychological effects of sexual assaults from around the globe as well as the influence of psychosocial therapies on these effects as this will have implications for rape survivors, policymakers, the government, non-governmental organizations and others. A literature review of five databases was searched to identify studies investigating the effectiveness of interventions focused on rape PTSD. Narrative synthesis was used to read across studies and the report was presented based on PRISMA checklist. Six studies met the eligibility criteria. Three studies investigated Eye Movement Desensitization Reprocessing (EMDR); the remaining studies assessed Cognitive Behavioural Therapy (CBT), Cognitive Processing Therapy (CPT) and Modified Lifespan Integration (MLI) respectively. Overall, there was substantial evidence supporting the effectiveness of EMDR, CPT, and MLI in both individual and group settings for reducing rape-related PTSD symptoms. However, there was insufficient and conflicting data supporting the use of early CBT therapies for PTSD due to rape, necessitating further research in this area.